Analisa Pengendalian Kualitas Proses Produksi Botol pada Departemen Blow Molding di Industri Packaging - admin CDMA; Neoninsa Risma Rossihanida; Renanda Nia Rachmadita; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
In the past one year, the problem of critical defects is the most dominant problem. With a percentage of 46% of all problems. This study aims to determine the factors that cause the bottle to leak and to find an effort to reduce the level of leaky bottles in the blow molding department's bottle production process. The method used in this study is Six Sigma which includes five stages of analysis, namely DMAIC (Define, Measure, Analyze, Improve, and Control). The approach used to improve the process. Each stage of DMAIC is done by carefully analyzing and maintaining the process. The results of this study indicate that the factors causing leaky bottles analyzed with FTA are problematic valves, air settings are not normal, blow pins are not centered, loose switch limit bolts, no checking rules, new technicians, and no defective mouth product reference . While the effort that must be done is changing the valve, the central pressure is increased to 7.5-8 bar, setting the blow pin to the center, changing the limit switch bolt, making the rules at the beginning of shift shifts, holding regular training for technicians, and making leaky product references.